PENURUNAN RISIKO OPERASIONAL PENGADAAN BARANG/JASA DI KEMENTERIAN PERINDUSTRIAN DENGAN METODE HOUSE OF RISK - gealovey azzahra; Vera Nova Lumban Raja; Tini Juartini (Universitas Krisnadwipayana, 2026)
This study aims to examine and mitigate operational risks in the procurement of goods and services at the Ministry of Industry. The research was carried out at the Procurement Unit of the Ministry of Industry in Jakarta, with data collected through interviews, observations. The applied method is the House of Risk (HOR), which consists of two stages: HOR 1 to identify risks and determine priority risk agents based on the Aggregate Risk Priority (ARP) value, and HOR 2 to formulate mitigation strategies by considering the effectiveness-to-difficulty ratio (ETD). The findings reveal 20 categories of goods and 17 categories of services with a total procurement value of IDR 2.37 billion, while estimated losses due to operational risks amounted to IDR 48 million, or approximately 2% of the total value. The implementation of the HOR method successfully reduced the number of risk incidents from 23 to 10 cases and decreased the loss value by IDR 216.4 million, equivalent to 56.5%. Thus, it can be concluded that the House of Risk method is effective in supporting the development of more reliable, efficient, and low-risk procurement strategies, while also enhancing operational risk management within the Ministry of Industry.